Preparation and application of degradable polyester and anti-radiation material based on methylparaben
By synthesizing a degradable polyester P based on methylparaben by using 2,5-furandimethyl alcohol, homemade new diester monomer M and dimethyl pyrazine-2,5-dicarboxylate, the problems of environmental pollution and poor radiation resistance of existing polyester products are solved, and a polyester composite material with high mechanical properties and excellent radiation resistance is achieved.
Patent Information
- Application Number
- CN202311083149.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
The large amount of petroleum-based raw materials used in existing polyester products leads to environmental pollution, poor mechanical properties and degradation properties, and poor shielding ability of radiation-proof composite materials.
2,5-furandimethyl alcohol, homemade new diester monomer M and pyrazine-2,5-dicarboxylic acid dimethyl ester are used as raw materials to synthesize the degradable polyester P based on methylparaben ester through transesterification and catalytic polycondensation reaction, and further processed into a high-toughness composite material for the preparation of radiation-proof clothing and other products.
It achieves the high mechanical properties and good degradation properties of polyester, has excellent radiation resistance, and is suitable for the base material production of radiation-proof clothing, jackets, vests, sheaths, raincoats and other products.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation and application of a degradable polyester and radiation-proof material based on methylparaben, belonging to the field of preparation of degradable polymers and radiation-proof materials. Methylparaben is used as one of the raw materials to obtain a degradable polyester P based on methylparaben, which is used to prepare environmentally friendly shopping bags, environmentally friendly food packaging bags, takeout boxes, and packaging bottles / barrels for food, drinking water, and beverages. The polyester can also be processed into an organic-inorganic composite material to produce a high-toughness composite material with good toughness and excellent radiation protection, which is further used to make the base material for radiation-proof clothing, radiation-proof jackets, radiation-proof vests, radiation-proof sheaths, and radiation-proof raincoats. Background Art
[0002] Radiation can affect human health. When exposed to ionizing radiation, if enough cells in tissues or organs are damaged, certain biological effects can occur. Mild symptoms include skin redness and swelling, clouding of the lens of the eye, dizziness, nausea, and hair loss. Severe cases can cause organ damage and failure, infertility, cancer, and even death. Radiation protection materials can weaken or prevent radiation damage from radioactive sources, thereby promoting the widespread application of nuclear technology. Therefore, the development of efficient and multifunctional radiation protection materials has become a focus of scientific research. Generally speaking, radiation protection materials need to be non-toxic, lightweight, have a wide shielding range, long-lasting shielding performance, and be corrosion-resistant. Currently, most radiation shielding materials are concrete and metals (such as lead, tungsten, and iron). With the advancement of nuclear energy technology, it has been found that traditional shielding materials cannot meet the shielding requirements of certain specific applications. For example, lead is toxic and has poor neutron shielding effectiveness, while concrete is bulky and difficult to move. Therefore, to meet the challenges posed by this, the development of new radiation shielding materials that are non-toxic, low-density, have excellent shielding effectiveness, and possess superior physical properties has become a key aspect of materials research and development. [1] ([1] Gao Jing, Ding Qianxue, Mei Qiliang, Xiao Xueshan, Research progress of nuclear radiation comprehensive shielding materials [J]. Materials Review, 2023, 37(20): 21120255). Compared with traditional concrete and heavy metal shielding materials, polymer-based radiation protection materials prepared by adding lead powder or other shielding fillers with polymer resin as the matrix have the advantages of easy shaping, light weight and relatively low price, showing broader application prospects in aerospace, nuclear power plants and medical devices.
[0003] Anti-radiation clothing refers to clothing and accessories that can shield electromagnetic radiation. With the development of science and technology, anti-radiation fabric fibers and production processes are constantly being innovated. Materials have expanded from metal wire and metal fiber to graphite, carbon fiber, metal and metal oxide powders, polymer conductive materials, etc., gradually improving the defects of early anti-radiation fabrics such as heavy weight, high cost and low efficiency, making the fabric lighter, softer, more breathable and moisture-absorbing, and also washable, greatly improving the efficiency of electromagnetic shielding. Therefore, anti-radiation clothing is becoming more and more popular. [2] ([2] Liu Dan. Fashionable design of anti-radiation clothing [J]. Textile Report, 2021, 40(12): 59-61.).
[0004] Zhao Sheng [3] ([3] Zhao Sheng, Huo Zhipeng, Zhong Guoqiang, et al. Preparation of modified gadolinium / boron / polyethylene nanocomposites and their shielding properties against neutrons and gamma rays [J]. Journal of Chemistry in Universities, 2022, 43(6): 57-67.) et al. used the coupling agent γ-methacryloxypropyltrimethoxysilane to coat and modify nano-gadolinium oxide, and prepared a new type of modified nano-gadolinium oxide / boron carbide / high-density polyethylene composite material by hot pressing. The results showed that the compatibility and dispersibility of the modified product cross section were significantly improved, and the shielding rate of neutrons and gamma rays could be effectively improved. Summary of the Invention
[0005] In response to the problems in the prior art of polyester products such as the adverse effects on the environment caused by the large-scale use of petroleum-based raw materials, poor mechanical properties and degradation properties, and poor shielding ability of radiation-proof composite materials, the present invention uses 2,5-furan dimethanol as an alcohol source, a homemade new diester monomer M as a first ester source, and pyrazine-2,5-dicarboxylic acid dimethyl ester as a second ester source, and obtains a degradable polyester P product based on methyl paraben after ester exchange and catalytic polycondensation reaction after purification. The product is used to prepare environmentally friendly shopping bags, environmentally friendly food packaging bags, takeout packaging boxes, and packaging bottles / barrels for food, drinking water, and beverages; it can also be processed into an organic-inorganic composite material to obtain a high-toughness composite material with good toughness and excellent radiation protection, which is further used to make the base material of radiation-proof clothing, radiation-proof jackets, radiation-proof vests, radiation-proof sheaths, and radiation-proof raincoats.
[0006] To achieve the purpose of the present invention, the present invention adopts the following technical solutions.
[0007] To better implement the technical solution of the present invention, the present invention discloses the preparation and application of a biodegradable polyester and a radiation-proof material based on renewable methyl paraben. The preparation method of the biodegradable polyester P and the radiation-proof material based on methyl paraben comprises the following steps.
[0008] 1. A degradable polyester P based on methyl paraben, characterized by having a structure as shown in Formula 1.
[0009] .
[0010] Where: x in formula 1 is 56~68, and y is 70~75.
[0011] 2. A method for preparing a degradable polyester P based on methylparaben, characterized in that the preparation method comprises the following steps.
[0012] 1) Synthesis of diester monomer M: A certain amount of methyl paraben (CAS No. 99-76-3), a certain amount of bromo(bromomethoxy)methane (CAS No. 4497-29-4), and potassium carbonate were added to a reactor at a molar ratio of 2:(1.0-1.2):1. N,N-dimethylformamide was added to dissolve the reaction mixture. The reaction mixture was stirred at 70-75°C for 1-2 hours. The reaction mixture was poured into cold water and stirred for 0.5 hours. After standing for 0.5 hours, it was filtered. The resulting solid was washed with deionized water until neutral. The filtered solid was dried in an oven at 50-70°C for 1-2 hours to obtain a diester monomer M. The structural formula of diester monomer M is shown in Formula 2.
[0013] .
[0014] 2) Synthesis of crude polyester: 2,5-furan dimethanol (CAS No. 1883-75-6) is used as an alcohol source, diester monomer M is used as a first ester source, and dimethyl pyrazine-2,5-dicarboxylate (CAS No. 13051-89-3) is used as a second ester source. These raw materials are added to a reactor at a certain molar ratio of 10:(4.8~5):(4.8~5). A catalyst is added, and nitrogen is passed through. An ester exchange reaction is carried out at 160~175°C with stirring for 2~4 hours to obtain an ester exchange product. The temperature is further increased to 210~235°C, and the absolute pressure of the reaction system is controlled at 85~120 Pa. A polycondensation reaction is carried out with stirring for 2~4 hours to obtain a crude polyester.
[0015] 3) Purification of crude polyester: The crude polyester was dissolved in chloroform, filtered, and the supernatant was collected. An appropriate amount of methanol was added to the supernatant until the precipitate no longer increased. The supernatant was filtered, and the resulting solid was washed with methanol. The washed solid was dried in an oven at 60-75°C for 1-2 hours to obtain a biodegradable polyester P based on methyl paraben.
[0016] 3. A method for preparing a biodegradable polyester P based on methylparaben, characterized in that: the catalyst described in step 2) is one of stannous octoate T-9, dibutyltin dilaurate T-12, tributyltin oxide, and dibutyltin dichloride, and the amount of the catalyst added to the reaction system is 0.02% to 0.15% of the amount of 2,5-furan dimethanol.
[0017] 4. Preparation method of methylparaben-based degradable polyester P: The prepared degradable polyester P is used to prepare environmentally friendly shopping bags, environmentally friendly food packaging bags, takeout boxes, and packaging bottles / barrels for food, drinking water, and beverages; the preparation method is characterized in that the methylparaben-based degradable polyester P is prepared into a 0.025-0.1 mm polyester plastic film by a blow molding process, or is prepared into a 0.25-2.5 mm polyester plastic bottle by a blow molding process, which is further used to make environmentally friendly shopping bags, environmentally friendly food packaging bags, or packaging containers for bottled food, water, and beverages.
[0018] 5. Preparation method of degradable polyester P based on methyl paraben. The degradable polyester P prepared is used to prepare high-toughness composite materials and radiation protection materials.
[0019] 100 parts by weight of a biodegradable polyester P based on methyl paraben, 20 parts by weight of 2,4,6-trimethylbenzenesulfonylhydrazine with a CAS number of 16182-15-3 as a foaming agent, 5 parts by weight of N,N-methylenebisacrylamide with a CAS number of 110-26-9 as a cross-linking agent, 20-30 parts by weight of Ag2S, 10 parts by weight of zinc oxide, 10 parts by weight of aluminum oxide, 10 parts by weight of barium titanate, and 1.5-2 parts by weight of tapic acid are put into an internal mixer at once, the temperature is controlled at 120-140°C, the internal mixer is mixed for half an hour, and the mixture is transferred to a foaming mold for cross-linking and foaming. The foaming temperature is controlled at 170°C and the foaming time is 1 hour to prepare a high-toughness composite material, which is further used for preparing a base material for radiation-proof clothing, radiation-proof jackets, radiation-proof vests, radiation-proof sheaths, and radiation-proof raincoats.
[0020] Beneficial effects.
[0021] 1. This patent uses renewable 2,5-furan dimethanol, renewable homemade new diester monomer M, and renewable pyrazine-2,5-dicarboxylic acid dimethyl ester as raw materials to prepare polyester, replacing petroleum-based monomers as the basic raw materials for preparing polyester, which is conducive to the implementation of the "dual carbon" national policy of carbon emission reduction and carbon neutrality, and the product has significant environmental protection characteristics.
[0022] 2. Cheng Huiqiang [4]([4] Cheng Huiqiang, Xiang Yang, Pan Yang, et al. Preparation and impact properties of polycarbonate / polybutylene terephthalate alternating layered composite materials [J]. Polymer Materials Science and Engineering, 2023, 1(43): 1-10.) A polycarbonate / polybutylene terephthalate alternating layered composite material was reported to have a flexural strength of 55 MPa, a tensile strength of 57 MPa, and an elongation at break of 200% to 215%. The number average molecular weight of the polyester P based on methyl paraben prepared in the present invention is 4.38×10 4 ~4.76×10 4 g / mol, the flexural strength is 94.6-122.7 MPa, the tensile strength is 75.9-96.8 MPa, and the elongation at break is 291.3%-327.5%. The elasticity of the polyester is greatly enhanced, so that the polyester prepared by the present invention has good ductility and is easier to be processed into products with performance that meets use requirements. The next step is to process it into radiation-proof materials. The characteristics of light weight and good toughness make the materials made with it particularly suitable for the production of base materials for radiation-proof clothing, radiation-proof jackets, radiation-proof vests, radiation-proof sheaths, and radiation-proof raincoats.
[0023] 3. Wu Ying [5] ([5] Wu Ying, Yao Ming, Wang Xiaotao, et al. Preparation and performance research of polyurethane-based flexible radiation shielding materials [J]. Journal of Beijing University of Chemical Technology (Natural Science Edition), 2023, 50(4): 37-41.) The preparation and performance research of a polyurethane-based flexible radiation shielding material were reported. The article stated that when the thickness of the composite material is 0.30 mm, the surface density is 1.48 kg / m2, and the tungsten powder loading is 92.0%, the shielding rate of the composite material for X-rays (120 kV) can reach 61.1%. The radiation-proof material prepared by the present invention can be directly processed into the required products with radiation-proof performance. As the Ag2S content in the polyester increases, the radiation-proof performance is better, and the shielding performance reaches 68.5%~70.9%. The characteristics of good toughness and good radiation protection effect make the material made from it suitable for the production of base materials for radiation-proof clothing, radiation-proof jackets, radiation-proof vests, radiation-proof sheaths, and radiation-proof raincoats.
[0024] 4. Ma Ying [6]([6] Ma Ying, Hou Wei, Su Tingting. Study on the enzymatic degradation performance of new automotive material poly (butylene succinate-co-adipate) copolyester [J]. Plastics Science and Technology, 2023, 51(1): 95-100.) It is reported that a poly (butylene succinate-co-adipate) copolyester needs to be hydrolyzed in a specific Na2HPO4-NaH2PO4 buffer containing cutinase. The biodegradable polyester P based on methyl paraben prepared by the present invention has good biodegradability. The degradability is determined according to the intrinsic viscosity value of the polyester. It is determined that the biodegradable polyester is buried in the soil of the natural environment after being discarded. It degrades by 2.1%~3.4% in the first year, 5.2%-8.0% in the second year, and 8.3%~12.5% in the third year. After natural degradation, it has no systematic impact on the environmental ecology and will not cause ecological damage. DETAILED DESCRIPTION
[0026] The present invention is further described below by way of examples, but the present invention is not limited by the examples. The raw materials in the present invention are all commercially available.
[0027] Mechanical properties test in the example: Tensile properties test: The tensile strength and elongation at break of the sample were tested with reference to GB / T 1040.2-2006. The tensile rate was set to 5 mm / min, and the results were taken as the average value of 5 samples; the bending properties were carried out in accordance with GB / T 9341-2008.
[0028] The intrinsic viscosity was measured with reference to GB / T 1632.5-2008. The test temperature was 25°C, the solvent was phenol / tetrachloroethane (50 / 50, wt / wt), the concentration of polyester was 0.5 g / dL, and the measurement was performed using an Ubbelohde viscometer.
[0029] The molecular weight test was performed using a Tosoh (Japan) HLC-8320GPC gel permeation chromatograph with THF as the mobile phase at a flow rate of 1 mL / min and a test temperature of 40°C to determine the number average molecular weight (Mn). The system was calibrated with polystyrene standards.
[0030] The results were the average of 5 test samples.
[0031] Shielding performance was evaluated by emitting 120 kV, 13 mA X-rays (average energy 100 keV) from an X-ray generator. The geometric center of the emitter and the center of the detector remained unchanged, and the air kerma ratio (H0) was obtained without shielding material. Then, shielding material was placed between the radiation source and the detector to obtain the air kerma ratio (H) with shielding material. The shielding efficiency η of the shielding material against X-rays was calculated according to formula (3).
[0032] .
[0033] ([5] Wu Ying, Yao Ming, Wang Xiaotao, et al. Preparation and performance research of polyurethane-based flexible radiation shielding materials [J]. Journal of Beijing University of Chemical Technology (Natural Science Edition), 2023, 50(04): 37-41.).
[0034] Example 1.
[0035] In the reactor, 10.350 g (0.068 mol) of methyl paraben, 6.840 g (0.034 mol) of bromo(bromomethoxy)methane, and 4.700 g (0.034 mol) of potassium carbonate were added in sequence according to the molar ratio, and 40 ml of N,N-dimethylformamide solvent was added to dissolve the reaction mixture. The reaction was stirred at 70°C for 1 hour, and the reaction mixture was poured into cold water and stirred for 0.5 hour. After standing for 0.5 hour, it was filtered and the obtained solid was washed with deionized water until neutral. The filtered solid was dried in an oven at 50°C for 1 hour. The mass of the diester monomer M obtained was 11.281 g, and the yield was 95.80%.
[0036] To a 50ml single-necked flask, 4.869g (0.038mol) of 2,5-furan dimethanol, 6.580g (0.019mol) of diester monomer M, 3.727g (0.019mol) of dimethyl pyrazine-2,5-dicarboxylate, and 0.0288g (0.000046mol) of dibutyltin dilaurate T-12 were added in sequence. Under nitrogen protection, the reaction was stirred at 160°C for 2 hours under atmospheric pressure to obtain the transesterification product. The temperature was then raised to 210°C, while maintaining the absolute pressure in the reaction system at approximately 85 Pa. The reaction was continued for 2 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform and filtered. The clear liquid was taken and an appropriate amount of methanol was added to the clear liquid until the precipitation stopped. The solid was washed with methanol and dried in an oven at 60°C for 1 hour to obtain 13.818 g of degradable polyester P1 based on methyl paraben with a yield of 91.05%. The number average molecular weight was 4.52×10 4 g / mol, flexural strength is 108.5MPa, tensile strength is 86.4MPa, and elongation at break is 309.8%.
[0037] The degradable polyester P1 prepared by the preparation method of methylparaben is used to prepare environmentally friendly shopping bags. The method is to prepare it into a 0.03mm polyester plastic film through a blow molding process, which is further used to make environmentally friendly shopping bags. The degradation performance of this type of environmentally friendly shopping bags shows that the degradation performance of the degradable polyester P1 based on methylparaben is measured according to the intrinsic viscosity value of the polyester and calculated according to the formula in Table 1. The degradation is 3.3% in the first year, 7.7% in the second year, and 12.1% in the third year. The specific data are shown in Table 1.
[0038] Preparation of high-toughness composite materials: Take 100g of degradable polyester P1 based on methyl paraben, 20g of 2,4,6-trimethylbenzenesulfonyl hydrazide as a foaming agent, 5g of N,N-methylenebisacrylamide as a cross-linking agent, 20g of Ag2S, 10g of zinc oxide, 10g of aluminum oxide, 10g of barium titanate, and 2g of tapic acid. All the above raw materials are put into an internal mixer at one time, the temperature is controlled at 130°C, and after mixing for half an hour, they are transferred to a foaming mold for cross-linking and foaming. The foaming temperature is controlled at 170°C and the foaming time is 1 hour to obtain a high-toughness composite material P10.
[0039] The high-toughness composite material P10 has a shielding rate of η=68.5% after testing, which meets the conditions for sufficient radiation protection. It is a high-toughness composite material with good radiation protection performance and is further used in the production of base materials for radiation protection clothing.
[0040] Example 2.
[0041] In the reactor, 10.350 g (0.068 mol) of methyl paraben, 7.624 g (0.0374 mol) of bromo(bromomethoxy)methane, and 4.700 g (0.034 mol) of potassium carbonate were added in sequence according to the molar ratio, and 40 ml of N,N-dimethylformamide solvent was added to dissolve the reaction mixture. The reaction was stirred at 70°C for 1.5 hours. The reaction mixture was poured into cold water and stirred for 0.5 hours. After standing for 0.5 hours, it was filtered and the obtained solid was washed with deionized water until neutral. The filtered solid was dried in an oven at 50°C for 1.5 hours. The mass of the diester monomer M obtained was 11.022 g, and the yield was 93.60%.
[0042] To a 50ml single-necked flask, 4.356g (0.034mol) of 2,5-furan dimethanol, 5.541g (0.0163mol) of diester monomer M, 3.335g (0.017mol) of dimethyl pyrazine-2,5-dicarboxylate, and 0.0258g (0.000041mol) of dibutyltin dilaurate T-12 were added in sequence. Under nitrogen protection, the reaction was stirred at 165°C for 3 hours under atmospheric pressure to obtain the transesterification product. The temperature was then raised to 220°C, while maintaining the absolute pressure in the reaction system at approximately 100 Pa. The reaction was continued for 3 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform and filtered. The clear liquid was taken and an appropriate amount of methanol was added to the clear liquid until the precipitation stopped. The solid was washed with methanol and dried in an oven at 75°C for 2 hours to obtain 11.889 g of polyester P2 based on methyl paraben with a yield of 89.85%. The number average molecular weight was 4.38×10 4 g / mol, flexural strength is 94.6MPa, tensile strength is 75.9MPa, and elongation at break is 291.3%.
[0043] The degradable polyester P2 prepared by the preparation method of methylparaben is used to prepare environmentally friendly food packaging bags. The method is to prepare it into a 0.05mm polyester plastic film through a blow molding process, which is further used for the production of environmentally friendly food packaging bags. The degradation performance of this type of environmentally friendly food packaging bags shows that the degradation performance of the degradable polyester P2 based on methylparaben is determined according to the intrinsic viscosity value of the polyester and calculated according to the formula in Table 1. The degradation is 3.4% in the first year, 8.0% in the second year, and 12.5% in the third year. The specific data are shown in Table 1.
[0044] Preparation of high-toughness composite materials: Take 100g of degradable polyester P2 based on methyl paraben, 20g of 2,4,6-trimethylbenzenesulfonyl hydrazide as a foaming agent, 5g of N,N-methylenebisacrylamide as a cross-linking agent, 22g of Ag2S, 10g of zinc oxide, 10g of aluminum oxide, 10g of barium titanate, and 2g of tapic acid. All the above raw materials are put into an internal mixer at one time, the temperature is controlled at 130°C, and the internal mixer is mixed for half an hour, and then transferred to a foaming mold for cross-linking and foaming. The foaming temperature is controlled at 170°C and the foaming time is 1 hour to obtain a high-toughness composite material P20.
[0045] The high-toughness composite material P20 has a shielding rate of η=68.9% after testing, which meets the conditions for sufficient radiation protection. It is a high-toughness composite material with good radiation protection performance, and is further used in the production of base materials for radiation protection jackets.
[0046] Example 3.
[0047] In the reactor, 10.350 g (0.068 mol) of methyl paraben, 8.318 g (0.0408 mol) of bromo(bromomethoxy)methane, and 4.700 g (0.034 mol) of potassium carbonate were added in sequence according to the molar ratio, and 40 ml of N,N-dimethylformamide solvent was added to dissolve the reaction mixture. The reaction was stirred at 70°C for 2 hours, and the reaction mixture was poured into cold water and stirred for 0.5 hours. After standing for 0.5 hours, it was filtered and the obtained solid was washed with deionized water until neutral. The filtered solid was dried in an oven at 50°C for 2 hours to obtain a diester monomer M with a mass of 11.387 g and a yield of 96.70%.
[0048] To a 50 ml single-necked flask, 4.613 g (0.036 mol) of 2,5-furan dimethanol, 6.096 g (0.0176 mol) of diester monomer M, 3.452 g (0.0176 mol) of dimethyl pyrazine-2,5-dicarboxylate, and 0.0215 g (0.000036 mol) of tributyltin oxide were added in sequence. Under nitrogen protection, the reaction was stirred at 175°C for 4 hours under atmospheric pressure to obtain the transesterification product. The temperature was then raised to 235°C, while maintaining the absolute pressure in the reaction system at approximately 120 Pa. The reaction was continued for 4 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform and filtered. The clear liquid was taken and an appropriate amount of methanol was added to the clear liquid until the precipitation stopped increasing. The solid was washed with methanol and dried in an oven at 75°C for 1 hour to obtain 12.855 g of degradable polyester P3 based on methyl paraben with a yield of 91.83%. The number average molecular weight was 4.43×10 4 g / mol, flexural strength is 99.2MPa, tensile strength is 78.2MPa, and elongation at break is 296.7%.
[0049] The degradable polyester P3 prepared by the preparation method of degradable polyester P3 based on methyl paraben is used to prepare environmentally friendly food packaging polyester bottles. The method is to prepare it into 0.8mm polyester plastic bottles through a blow molding process, which are further used for the production of environmentally friendly food packaging polyester bottles. The degradation performance of this type of environmentally friendly food packaging polyester bottles shows that the degradation performance of the degradable polyester P3 based on methyl paraben is determined according to the intrinsic viscosity value of the polyester and calculated according to the formula in Table 1. The degradation is 3.4% in the first year, 7.9% in the second year, and 12.4% in the third year. The specific data are shown in Table 1.
[0050] Preparation of high-toughness composite materials: Take 100g of degradable polyester P3 based on methyl paraben, 20g of 2,4,6-trimethylbenzenesulfonyl hydrazide as a foaming agent, 5g of N,N-methylenebisacrylamide as a cross-linking agent, 24g of Ag2S, 10g of zinc oxide, 10g of aluminum oxide, 10g of barium titanate, and 2g of tapic acid. All the above raw materials are put into an internal mixer at one time, the temperature is controlled at 130°C, and after mixing for half an hour, they are transferred to a foaming mold for cross-linking and foaming. The foaming temperature is controlled at 170°C and the foaming time is 1 hour to obtain a high-toughness composite material P30.
[0051] The high-toughness composite material P30 has a shielding rate of η=69.5% after testing, which meets the conditions for sufficient radiation protection. It is a high-toughness composite material with good radiation protection performance and is further used in the production of the base material of radiation protection vests.
[0052] Example 4.
[0053] In the reactor, 10.350 g (0.068 mol) of methyl paraben, 6.840 g (0.034 mol) of bromo(bromomethoxy)methane, and 4.700 g (0.034 mol) of potassium carbonate were added in sequence according to the molar ratio, and 40 ml of N,N-dimethylformamide solvent was added to dissolve the reaction mixture. The reaction was stirred at 75°C for 2 hours, and the reaction mixture was poured into cold water and stirred for 0.5 hours. After standing for 0.5 hours, it was filtered and the obtained solid was washed with deionized water until neutral. The filtered solid was dried in an oven at 70°C for 1 hour. The mass of the diester monomer M obtained was 10.622 g, and the yield was 90.2%.
[0054] To a 50 ml single-necked flask, 4.869 g (0.038 mol) of 2,5-furan dimethanol, 6.580 g (0.019 mol) of diester monomer M, 3.727 g (0.019 mol) of dimethyl pyrazine-2,5-dicarboxylate, and 0.0163 g (0.000054 mol) of dibutyltin dichloride were added in sequence. Under nitrogen protection, the reaction was stirred at 175°C for 3 hours at atmospheric pressure to obtain the transesterification product. The temperature was then raised to 230°C, while maintaining the absolute pressure in the reaction system at approximately 115 Pa. The reaction was continued for 2 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform and filtered. The clear liquid was taken and an appropriate amount of methanol was added to the clear liquid until the precipitation stopped increasing. The solid was washed with methanol and dried in an oven at 65°C for 2 hours to obtain 13.560 g of degradable polyester P4 based on methyl paraben with a yield of 89.35%. The number average molecular weight was 4.63×10 4 g / mol, flexural strength is 116.8MPa, tensile strength is 91.3MPa, and elongation at break is 318.4%.
[0055] The degradable polyester P4 prepared by the preparation method of methyl paraben is used to prepare environmentally friendly polyester barrels. The method is to prepare it into 1.75mm polyester plastic bottles through a blow molding process, which are further used in the production of environmentally friendly polyester barrels. The degradation performance of this type of environmentally friendly polyester barrels shows that the degradation performance of the degradable polyester P4 based on methyl paraben is determined according to the intrinsic viscosity value of the polyester and calculated according to the formula in Table 1. The degradation is 2.2% in the first year, 5.4% in the second year, and 8.6% in the third year. The specific data are shown in Table 1.
[0056] Preparation of high-toughness composite materials: Take 100g of degradable polyester P4 based on methyl paraben, 20g of 2,4,6-trimethylbenzenesulfonyl hydrazide as a foaming agent, 5g of N,N-methylenebisacrylamide as a cross-linking agent, 26g of Ag2S, 10g of zinc oxide, 10g of aluminum oxide, 10g of barium titanate, and 2g of tapic acid. All the above raw materials are put into an internal mixer at one time, the temperature is controlled at 130°C, and the internal mixer is mixed for half an hour, and then transferred to a foaming mold for cross-linking and foaming. The foaming temperature is controlled at 170°C and the foaming time is 1 hour to obtain a high-toughness composite material P40.
[0057] The high-toughness composite material P40 has a shielding rate of η=70.1% after testing, which meets the conditions for sufficient radiation protection. It is a high-toughness composite material with good radiation protection performance and is further used in the production of base materials for radiation protection sheaths.
[0058] Example 5.
[0059] In the reactor, 10.350 g (0.068 mol) of methyl paraben, 7.624 g (0.0374 mol) of bromo(bromomethoxy)methane, and 4.700 g (0.034 mol) of potassium carbonate were added in sequence according to the molar ratio, and 40 ml of N,N-dimethylformamide solvent was added to dissolve the reaction mixture. The reaction was stirred at 75°C for 1 hour, and the reaction mixture was poured into a large amount of cold water and stirred for 0.5 hour. After standing for 0.5 hour, it was filtered and the obtained solid was washed with deionized water until neutral. The filtered solid was dried in an oven at 70°C for 1.5 hours to obtain a diester monomer M with a mass of 10.775 g and a yield of 91.50%.
[0060] To a 50ml single-necked flask, 4.356g (0.034mol) of 2,5-furan dimethanol, 5.541g (0.0163mol) of diester monomer M, 3.335g (0.017mol) of dimethyl pyrazine-2,5-dicarboxylate, and 0.0103g (0.000034mol) of dibutyltin dichloride were added in sequence. Under nitrogen protection, the reaction was stirred at 160°C for 4 hours under atmospheric pressure to obtain the transesterification product. The temperature was then raised to 210°C, while maintaining the absolute pressure in the reaction system at approximately 100 Pa. The reaction was continued for 3 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform and filtered. The clear liquid was taken and an appropriate amount of methanol was added to the clear liquid until the precipitation stopped. The solid was washed with methanol and dried in an oven at 70°C for 2 hours to obtain 11.624 g of degradable polyester P5 based on methyl paraben with a yield of 87.85%. The number average molecular weight was 4.49×10 4 g / mol, flexural strength is 105.3MPa, tensile strength is 82.6MPa, and elongation at break is 304.2%.
[0061] The degradable polyester P5 prepared by the preparation method of methylparaben is used to prepare polyester bottles for environmentally friendly beverage packaging. The method is to prepare 1.25mm polyester plastic bottles through a blow molding process, which are further used to make polyester bottles for environmentally friendly beverage packaging. The degradation performance of such polyester bottles for environmentally friendly beverage packaging shows that the degradation performance of the degradable polyester P5 based on methylparaben is determined based on the intrinsic viscosity value of the polyester and calculated according to the formula in Table 1. The degradation is 3.3% in the first year, 7.8% in the second year, and 12.2% in the third year. The specific data are shown in Table 1.
[0062] Preparation of high-toughness composite materials: Take 100g of degradable polyester P5 based on methyl paraben, 20g of 2,4,6-trimethylbenzenesulfonyl hydrazide as a foaming agent, 5g of N,N-methylenebisacrylamide as a cross-linking agent, 28g of Ag2S, 10g of zinc oxide, 10g of aluminum oxide, 10g of barium titanate, and 2g of tapic acid. All the above raw materials are put into an internal mixer at one time, the temperature is controlled at 130°C, and the internal mixer is mixed for half an hour, and then transferred to a foaming mold for cross-linking and foaming. The foaming temperature is controlled at 170°C and the foaming time is 1 hour to obtain a high-toughness composite material P50.
[0063] The high-toughness composite material P50 has a shielding rate of η=70.5% after testing, which meets the conditions for sufficient radiation protection. It is a high-toughness composite material with good radiation protection performance, and is further used in the production of base materials for radiation-proof raincoats.
[0064] Example 6.
[0065] In the reactor, 10.350 g (0.068 mol) of methyl paraben, 8.318 g (0.0408 mol) of bromo(bromomethoxy)methane, and 4.700 g (0.034 mol) of potassium carbonate were added in sequence according to the molar ratio, and 40 ml of N,N-dimethylformamide solvent was added to dissolve the reaction mixture. The reaction was stirred at 75°C for 1.5 hours. The reaction mixture was poured into a large amount of cold water and stirred for 0.5 hours. After standing for 0.5 hours, it was filtered and the obtained solid was washed with deionized water until neutral. The filtered solid was dried in an oven at 60°C for 1.5 hours. The mass of the obtained diester monomer M was 11.105 g, and the yield was 94.30%.
[0066] To a 50ml single-necked flask, 4.613g (0.036mol) of 2,5-furan dimethanol, 6.096g (0.0176mol) of diester monomer M, 3.452g (0.0176mol) of dimethyl pyrazine-2,5-dicarboxylate, and 0.0175g (0.000043mol) of stannous octoate T-9 were added in sequence. Under nitrogen protection, the reaction was stirred at 170°C for 3 hours under atmospheric pressure to obtain the transesterification product. The temperature was then raised to 225°C, while maintaining the absolute pressure in the reaction system at approximately 90 Pa. The reaction was continued for 2 hours to obtain a crude polyester. The crude polyester was dissolved in chloroform and filtered. The clear liquid was taken and an appropriate amount of methanol was added to the clear liquid until the precipitation stopped. The solid was washed with methanol and dried in an oven at 60°C for 2 hours to obtain 12.763 g of degradable polyester P6 based on methyl paraben with a yield of 90.13%. The number average molecular weight was 4.76×10 4 g / mol, flexural strength is 122.7MPa, tensile strength is 96.8MPa, and elongation at break is 327.5%.
[0067] The degradable polyester P6 prepared by the preparation method of methylparaben is used to prepare environmentally friendly shopping bags. The method is to prepare it into a 0.07mm polyester plastic film through a blow molding process, which is further used for the production of environmentally friendly shopping bags. The degradation performance of this type of environmentally friendly shopping bags shows that the degradation performance of the degradable polyester P6 based on methylparaben is determined according to the intrinsic viscosity value of the polyester and calculated according to the formula in Table 1. The degradation is 2.1% in the first year, 5.2% in the second year, and 8.3% in the third year. The specific data are shown in Table 1.
[0068] Preparation of high-toughness composite materials: Take 100g of degradable polyester P6 based on methyl paraben, 20g of 2,4,6-trimethylbenzenesulfonyl hydrazide as a foaming agent, 5g of N,N-methylenebisacrylamide as a cross-linking agent, 30g of Ag2S, 10g of zinc oxide, 10g of aluminum oxide, 10g of barium titanate, and 2g of tapic acid. All the above raw materials are put into an internal mixer at one time, the temperature is controlled at 130°C, and the internal mixer is mixed for half an hour, and then transferred to a foaming mold for cross-linking and foaming. The foaming temperature is controlled at 170°C and the foaming time is 1 hour to obtain a high-toughness composite material P60.
[0069] The high-toughness composite material P60 has a shielding rate of η=70.9% after testing, which meets the conditions for sufficient radiation protection. It is a high-toughness composite material with good radiation protection performance, and is further used in the production of base materials for radiation protection jackets.
[0070] .
[0071] [4] Cheng Huiqiang, Xiang Yang, Pan Yang, et al. Preparation and impact properties of polycarbonate / polybutylene terephthalate alternating layered composites [J]. Polymer Materials Science and Engineering, 2023, 1(43): 1-10.
[0072] .
[0073] In Table 1, Mn is the number average molecular weight of the sample, [η0] is the initial test value of the intrinsic viscosity of the degradable polyester sample, [η1] is the test value of the intrinsic viscosity of the degradable polyester sample after degradation in the soil environment in the natural environment for one year, [η2] is the test value of the intrinsic viscosity of the degradable polyester sample after degradation in the soil environment in the natural environment for two years, and [η3] is the test value of the intrinsic viscosity of the degradable polyester sample after degradation in the soil environment in the natural environment for three years.
[0074] The calculation formula for the degradation rate in the first year is: r1= (η1-η0) / η0.
[0075] The calculation formula for the degradation rate in the second year is: r2= (η2-η0) / η0.
[0076] The calculation formula for the degradation rate in the third year is: r3= (η3-η0) / η0.
[0077] Comparison of the data in Table 1 shows that the biodegradable polyesters P1-P6 synthesized from the present invention using a diester monomer M synthesized from methylparaben and 2,5-furan dimethanol and dimethyl pyrazine-2,5-dicarboxylate as raw materials exhibit high number average molecular weights and tensile strengths 18.9-39.8 MPa higher than those of polybutylene terephthalate composites. A comparison of [η0] with [η1], [η2], and [η3] in Table 1 shows that the biodegradable polyesters synthesized in the present invention degrade in natural soil by 2.1%-3.4% in the first year, 5.2%-8.0% in the second year, and 8.3%-12.5% in the third year. This demonstrates that the molecular weight of the polyesters has been significantly reduced, making them susceptible to degradation by soil after disposal.
[0078] As can be seen from Table 2, the biodegradable polyester P synthesized from the diester monomer M synthesized based on methylparaben and 2,5-furan dimethanol and pyrazine-2,5-dicarboxylic acid dimethyl ester as raw materials is processed into a composite material. The composite material has good toughness and excellent radiation protection. As the Ag2S content increases, the shielding efficiency is higher and the radiation protection performance is better. It is further used for the production of base materials for radiation-proof clothing, radiation-proof jackets, radiation-proof vests, radiation-proof sheaths, and radiation-proof raincoats.
[0079] In summary, polyester products reported in existing literature suffer from defects such as poor mechanical and degradation properties, and inferior shielding capabilities of radiation-proof composite materials. To address these issues, the present invention primarily aims to provide the preparation and application of a degradable polyester and radiation-proof material based on methylparaben. Specifically, a methylparaben-based degradable polyester P is synthesized via transesterification and catalytic polycondensation using a diester monomer M synthesized from methylparaben with 2,5-furan dimethanol and dimethyl pyrazine-2,5-dicarboxylate. The degradable polyester P prepared in this invention is then processed into a composite material exhibiting excellent toughness and radiation protection, suitable for use as a base material for radiation-proof clothing, jackets, vests, jackets, and raincoats. Compared to existing composite materials, this composite material exhibits superior mechanical properties, flexibility, and excellent radiation protection. Therefore, the invention patent application for "Preparation and Application of Degradable Polyester and Radiation-Proofing Material Based on Methylparaben" is expected to have promising market prospects.
[0080] Although preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic inventive concepts. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the invention. Thus, the present invention is intended to include such changes and modifications as fall within the scope of the claims and their equivalents.
Claims
1. A degradable polyester P based on methyl paraben, characterized by It has a structure as shown in Formula 1: Wherein: x in formula 1 is 56~68, and y is 70~75.
2. A method for preparing a degradable polyester P based on methyl paraben, characterized in that The preparation method comprises the following steps: 1) Synthesis of diester monomer M: Take a certain amount of methyl paraben with CAS No. 99-76-3, a certain amount of bromo(bromomethoxy)methane with CAS No. 4497-29-4 and potassium carbonate, add them into a reactor according to the molar ratio of 2: (1.0~1.2): 1, add solvent N,N-dimethylformamide to dissolve the reaction mixture, stir and react at 70~75°C for 1-2 hours, pour the reaction mixture into cold water and stir for 0.5 hour, let it stand for 0.5 hour and filter, wash the obtained solid with deionized water until it is neutral, dry the filtered solid in an oven at 50~70°C for 1-2 hours, and obtain a diester monomer M. The structural formula of diester monomer M is shown in Formula 2: 2) Synthesis of crude polyester: 2,5-furan dimethanol with CAS number 1883-75-6 is used as an alcohol source, diester monomer M is used as a first ester source, and pyrazine-2,5-dicarboxylic acid dimethyl ester with CAS number 13051-89-3 is used as a second ester source. The above raw materials are added to a reactor according to a certain molar ratio of 10: (4.8~5): (4.8~5), and a catalyst is added. Under nitrogen protection, an ester exchange reaction is carried out at 160~175°C with stirring for 2~4 hours to obtain an ester exchange product. The temperature is further increased to 210~235°C, and the absolute pressure of the reaction system is controlled at 85~120Pa. A polycondensation reaction is carried out under stirring for 2~4 hours to obtain a crude polyester; 3) Purification of crude polyester: Dissolve the crude polyester with chloroform, filter, take the clear liquid, add an appropriate amount of methanol to the clear liquid until the precipitation no longer increases, filter, wash the obtained solid with methanol, and dry the washed solid in an oven at 60-75°C for 1-2 hours to obtain a degradable polyester P based on methyl paraben.
3. The method for preparing the degradable polyester P based on methyl paraben according to claim 2, characterized in that: The catalyst described in step 2) is one of stannous octoate T-9, dibutyltin dilaurate T-12, tributyltin oxide, and dibutyltin dichloride, and the amount of the catalyst added to the reaction system is 0.02% to 0.15% of the amount of 2,5-furan dimethanol.
4. The degradable polyester P prepared by the preparation method of the degradable polyester P based on methyl paraben according to claim 2 is used to prepare environmentally friendly shopping bags, environmentally friendly food packaging bags, take-out packaging boxes, packaging bottles / barrels for food, drinking water and beverages; its preparation is characterized by: The degradable polyester P based on methyl paraben is prepared into a polyester plastic film of 0.025-0.1 mm by a blow molding process, or is prepared into a polyester plastic bottle of 0.25-2.5 mm by a blow molding process, and is further used in the production of environmentally friendly shopping bags, environmentally friendly food packaging bags, or packaging containers for bottled food, water, and beverages.
5. The degradable polyester P prepared by the preparation method of the degradable polyester P based on methyl paraben according to claim 2 is used to prepare high-toughness composite materials and radiation protection materials: Take 100 parts by mass of the degradable polyester P based on methyl paraben prepared according to claim 2, 20 parts by mass of 2,4,6-trimethylbenzenesulfonyl hydrazide with CAS number 16182-15-3 as a foaming agent, 5 parts by mass of N,N-methylenebisacrylamide with CAS number 110-26-9 as a cross-linking agent, 20-30 parts by mass of Ag2S, 10 parts by mass of zinc oxide, 10 parts by mass of aluminum oxide, 10 parts by mass of barium titanate, and 1.5-2 parts by mass of tapic acid. All the above raw materials are put into an internal mixer at one time, the temperature is controlled to be 120-140°C, and after the internal mixing for half an hour, the mixture is transferred to a foaming mold for cross-linking and foaming. The foaming temperature is controlled to be 170°C and the foaming time is 1 hour to obtain a high-toughness composite material, which is further used for the production of base materials for radiation protection clothing, radiation protection jackets, radiation protection vests, radiation protection sheaths, and radiation protection raincoats.